Effect of Folic Acid Supplementation for Reducing Methotrexate Side Effects in Patients with Rheumatoid Arthritis: an Evidence-based Case Report - Athira Presialia; Bambang Setyohadi (Indonesia Rheumatology Association, 2021)
Background: Rheumatoid arthritis is a chronic inflammatory joint disease, indicated by a symmetrical erosive synovitis. Disease-modifying anti-rheumatic drugs (DMARDs) are known to interfere with signs and symptoms of RA, improve physical function and therefore increase patient productivity. Methotrexate is an anchor drug for rheumatoid arthritis patients, however, its related mechanism of action with folate deficiency resulting in some side effects, including gastrointestinal and liver toxicity. Folic acid supplementation may reduce these side effects. Method: A search was conducted on Pubmed, Cochrane, EBSCOhost, and ProQuest. After the selection of title and abstract was done using inclusion and exclusion criteria, which led to one relevant article. The selected study was critically appraised for its validity, importance, and applicability. Result: In rheumatoid arthritis patient receiving methotrexate, there was a statistically significant reduction in the incidence of abnormal transaminase elevation (RR: 0.19, 95% CI: 0.10-0.36), but the reduction in gastrointestinal side effects did not reach statistical significance (RR: 0.76, 95% CI: 0.57-1.01) Conclusion: Folic acid supplementation has an effect in reducing gastrointestinal and liver toxicity as side effects of methotrexate in rheumatoid arthritis patients.